Pengaruh Penggunaan E-Booklet “Bahaya Narkoba” Dalam Membina Siswa Sekolah Dasar Untuk Menjadi Generasi Muda Yang Berkarakter - Jihan Qotrunada Salsabilla; Winti Ananthia; Yayang Furi Furnamasari (Jurnal Bintang Pendidikan Indonesia, 2023)
This research is motivated by the rise of drug abuse in Indonesia, one of which is caused by a lack of understanding of adolescents about the dangers of drugs, therefore understanding the dangers of drugs should be done as early as possible starting from elementary school level and fostering elementary school students to become young people with character and towards the golden generation. Thus, the need for media that can help elementary school students in understanding the dangers of drugs and character generation. The purpose of this study was to determine the effect of the use of e-book “The Dangers of Drugs” and to determine the difference in the ability to understand the dangers of drugs and character generation by using e-book “The Dangers of Drugs”. The research method used is pre-experimental design with research design using one group pre - test-post test design. The population in this study is all students of SDN Tebet Timur 15 morning and SDN Manggarai Selatan 01. The sample was 28 students of Grade 5 SDN Tebet Timur 15 am and 28 students of Grade 5 SDN Manggarai Selatan 01. The results showed 1) the influence of the use of e-book “The Dangers of Drugs” in fostering students to become a younger generation of character based on the results of posttest data analysis and questionnaires and 2) there are differences in the ability to understand the dangers of drugs and character generation by using e-book “The Dangers of Drugs” based on the results of pretest and posttest data analysis.